2020
DOI: 10.1101/2020.09.20.20196907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microfluidic Affinity Profiling reveals a Broad Range of Target Affinities for Anti-SARS-CoV-2 Antibodies in Plasma of COVID-19 Survivors

Abstract: The clinical outcome of SARS-CoV-2 infections can range from asymptomatic to lethal, and is thought to be crucially shaped by the quality of the immune response which includes antibody titres and affinity for their targets. Using Microfluidic Antibody Affinity Profiling (MAAP), we determined the aggregate affinities and concentrations of anti-SARS-CoV-2 antibodies in plasma samples of 42 seropositive individuals, 23 of whom were confirmed to be SARS-CoV-2-positive by PCR testing. We found that dissociation con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…In resource‐constrained settings, it is hence possible to orient the wave of CCP donations so that time and resource wasting is minimized. This study was limited to clinical proxies, but several studies identified additional, serological (eg, anti‐Spike IgG avidity, r = .4, 22 or microfluidic affinity) 23 or non‐serological biomarkers (eg, high C‐reactive protein, r = .5) 15 : The utility of such specialistic laboratory biomarkers is reduced by their limited availability at the time of CCP donation screening, and, if unavailable, by their incremental cost, which largely overlap the one of high‐throughput serology.…”
Section: Discussionmentioning
confidence: 99%
“…In resource‐constrained settings, it is hence possible to orient the wave of CCP donations so that time and resource wasting is minimized. This study was limited to clinical proxies, but several studies identified additional, serological (eg, anti‐Spike IgG avidity, r = .4, 22 or microfluidic affinity) 23 or non‐serological biomarkers (eg, high C‐reactive protein, r = .5) 15 : The utility of such specialistic laboratory biomarkers is reduced by their limited availability at the time of CCP donation screening, and, if unavailable, by their incremental cost, which largely overlap the one of high‐throughput serology.…”
Section: Discussionmentioning
confidence: 99%
“…In this assay, we used trimeric spike accounting not only the neutralizing antibodies targeting RBD sequence, but also additional epitopes which are suspected to contribute to the overall antibody response (9,11,33,34). To validate the assay, we used serum collected from 19 SARS-CoV-2 positive individuals 11-24 days after RT-PCR testing, a time window when seroconversion has been shown to occur (35)(36)(37)(38) and consistent with these previous reports, all but one of the 19 SARS-CoV-2 had seroconverted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it would have been logistically difficult to screen asymptomatic individuals outside a health care environment. It is a fact that we have used a limited number of SARS-CoV-2-positive individuals to setup our assays, however the number used is well within the one used in similar studies (3,11,31,32). In addition, variations of this ELISA test developed by Florian Krammer laboratory has been used by multiple groups worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the RBD-beta-ACE2 complex lacks salt bridges between RBD-beta K417 and ACE2 D30 and between RBD-beta E484 and ACE2 K31, which seems to counteract the increased ACE2 affinity mediated by N501Y 16 . 18,19 . Error bars are 95% credible intervals.…”
Section: Pmentioning
confidence: 99%